Effectiveness of training health professionals to provide smoking cessation interventions: systematic review of randomised controlled trials. Issue 4 (December 1994) - Silagy, C; Lancaster, T; Gray, S; Fowler, G
Abstract : OBJECTIVE--To assess the effectiveness of interventions that train healthcare professionals in methods for improving the quality of care delivered to patients who smoke. DESIGN--Systematic literature review. SETTING--Primary care medical and dental practices in the United States and Canada. Patients were recruited opportunistically. SUBJECTS--878 healthcare professionals and 11, 228 patients who smoked and were identified in eight randomised controlled trials. In each of these trials healthcare professionals received formal training in smoking cessation, and their performance was compared with that of a control group. MAIN MEASURES--Point prevalence rates of abstinence from smoking at six or 12 months in patients who were smokers at baseline. Rates of performance of tasks of smoking cessation by healthcare professionals, including offering counselling, setting dates to stop smoking, giving follow up appointments, distributing self help materials, and recommending nicotine gum. METHODS--Trials were identified by multiple methods. Data were abstracted according to predetermined criteria by two observers. When possible, meta-analysis was performed using a fixed effects model and the results were subjected to sensitivity analysis. RESULTS--Healthcare professionals who had received training were significantly more likely to perform tasks of smoking cessation than untrained controls. There was a modest increase in the odds of stopping smoking for smokers attending health professionals who had received training compared with patients attending control practitioners (odds ratio 1.35 (95% confidence interval 1.09 to 1.68)). This result was not robust to sensitivity analysis. The effects of training were increased if prompts and reminders were used. There was no definite benefit found for more intensive forms of counselling compared with minimal contact strategies. CONCLUSIONS--Training health professionals to provide smoking cessation interventions had a measurable impact on professional performance. A modest, but non-robust, effect on patient outcome was also found, suggesting that training alone is unlikely to be an effective strategy for improving quality of care, unless organisational and other factors are also considered.